Trade Reform in the CEMAC : Developments and Opportunities - Tsangarides, Charalambos (IMF Working Papers; Working Paper ;, 2007)
This paper provides an update on the main elements of the reform agenda concerning the CEMAC trade regime as well as a tentative quantitative assessment of selected effects on tariff revenues and trade patterns. Notwithstanding data limitations, the key messages from the analysis are as follows. First, there is a need for a renewed political commitment to regional integration. In addition, key measures for improving compliance with the requirements for a customs union need to be introduced, including limiting tariff exemptions, phasing out remaining surcharges, strengthening the determination of products' country origin, and enhancing customs administration. There is also a need to improve transportation infrastructure and organization. Finally, there is a strong case for tariff reduction, with or without an EPA. Trade liberalization would help boost economic growth and poverty alleviation and limit risks of trade diversion with an EPA. Tariff reform should be complemented by improvements in domestic revenue mobilization.